Platelet Deficiency Represents a Modifiable Risk Factor for Periprosthetic Joint Infection in a Preclinical Mouse Model. (2nd June 2021) - Greig, Danielle; Trikha, Rishi; Sekimura, Troy; Cevallos, Nicolas; Kelley, Benjamin V.; Mamouei, Zeinab; Yeaman, Michael R.; Bernthal, Nicholas M.
Abstract : Background: Well known for their hemostatic function, platelets are increasingly becoming recognized as important immunomodulators. The purpose of the present study was to assess the impact of platelet depletion on antimicrobial host defense in a mouse model of periprosthetic joint infection (PJI). Methods: Thrombocytopenia (TCP) was induced in C57BL/6 mice with use of a selective antibody against platelet CD41 (anti-CD41). Whole blood from pre-treated mice was incubated with Staphylococcus aureus to assess antimicrobial efficacy with use of bioluminescent imaging, quantitative histological staining, and colony forming unit (CFU) quantification. In parallel, untreated heterologous platelets were added to TCP blood to assess potential rescue of antimicrobial efficacy. In vivo, TCP and control mice underwent placement of a titanium implant in the femur inoculated with bioluminescent Xen36 S. aureus . Longitudinal bioluminescent imaging was performed postoperatively to quantify the evolution of bacterial burden, which was confirmed via assessment of S. aureus CFUs on the implant and in peri-implant tissue on postoperative day (POD) 28. Results: Anti-CD41 treatment resulted in significant dose-dependent reductions in platelet count. Ex vivo, platelet-depleted whole blood demonstrated significantly less bacterial reduction than control blood. These outcomes were reversed with the addition of untreated rescue platelets. In vivo, infection burden was significantly higher in TCP mice and was inversely correlated with preoperative platelet count (r 2 = 0.63, p = 0.037). Likewise, CFU quantification on POD28 was associated with increased bacterial proliferation and severity of periprosthetic infection in TCP mice compared with controls. Conclusions: Thrombocytopenia resulted in an increased bacterial burden both ex vivo and in vivo in a mouse model of PJI. Clinical Relevance: In orthopaedic patients, deficiencies in platelet quantity or function represent an easily modifiable risk factor for PJI.